Development of Project-Based Short Story Reading Module to Enhance 21st Century Skills of Junior High School Learners - Sari, Diana; Sinaga, Mangatur; Charlina, Charlina (FKIP - Universitas Riau, 2026)
This study aims to develop a project-based short story reading module to improve 21st-century skills in junior high school students. In the Merdeka Curriculum, students are required to master the 4Cs—critical thinking, creativity, collaboration, and communication—through active and meaningful learning. Short stories were chosen because of their simple structure, appeal, and ability to foster analytical skills and moral understanding. The project-based approach encourages students to engage in collaborative activities, problem solving, and creative work. The research used the Research and Development (R&D) method with the ADDIE model. Data was obtained through pre-tests and post-tests as well as interviews with teachers and students. Expert validation of the material, language, media, and cultural aspects showed an average suitability of 93.98% (very suitable). Limited trials with 60 students showed a significant increase in 4C skills, especially collaboration and communication. Student responses showed an average of 87.5%, indicating that the module was easy to understand, increased interest in reading, and fostered confidence in presentations. Overall, this project-based short story reading module proved to be valid, practical, and effective in supporting the development of 21st-century skills and creating more engaging and meaningful reading learning.